2016
DOI: 10.1038/srep19819
|View full text |Cite
|
Sign up to set email alerts
|

Nimbolide inhibits pancreatic cancer growth and metastasis through ROS-mediated apoptosis and inhibition of epithelial-to-mesenchymal transition

Abstract: The mortality and morbidity rates of pancreatic cancer are high because of its extremely invasive and metastatic nature. Its lack of symptoms, late diagnosis and chemo–resistance and the ineffective treatment modalities warrant the development of new chemo–therapeutic agents for pancreatic cancer. Agents from medicinal plants have demonstrated therapeutic benefits in various human cancers. Nimbolide, an active molecule isolated from Azadirachta indica, has been reported to exhibit several medicinal properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 46 publications
7
96
0
Order By: Relevance
“…7E, 7F), which revealed that the DET-induced autophagy was ROS-dependent. Since autophagy can play both positive and negative roles in tumor cell growth [19, 20], the autophagy inhibitor, chloroquine, was also used in MTT assays to elucidate its role. Nevertheless, autophagy inhibition did not alter the decrease in cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7E, 7F), which revealed that the DET-induced autophagy was ROS-dependent. Since autophagy can play both positive and negative roles in tumor cell growth [19, 20], the autophagy inhibitor, chloroquine, was also used in MTT assays to elucidate its role. Nevertheless, autophagy inhibition did not alter the decrease in cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there are currently no published results for clinical trials investigating capsaicin or EGCG in PanCA patients. New studies of natural products, have begun exploring the anti-cancer properties of plant extracts and compounds such as Nexrutine® (Nx), sulforaphane, and Nimbolide in PanCA [103108]. All three of these natural products have been demonstrated to have clinical potential as they exhibit strong anti-cancer effects in vitro [104108].…”
Section: Natural Productsmentioning
confidence: 99%
“…New studies of natural products, have begun exploring the anti-cancer properties of plant extracts and compounds such as Nexrutine® (Nx), sulforaphane, and Nimbolide in PanCA [103108]. All three of these natural products have been demonstrated to have clinical potential as they exhibit strong anti-cancer effects in vitro [104108]. In addition, Nimbolide and sulforaphane have been demonstrated to strongly reduce the size to PanCA xenografts in athymic mice [107, 108].…”
Section: Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…FDA granted necuparanib treatment of pancreatic cancer, which is derived from the unfractionated heparin; it is designed to significantly reduce the anticoagulant activity while preserving antitumor properties related. In herbal medicine (29), India Melia lactone can induce cancer cell death, led to the colony size and number of pancreatic cancer cells decreased by 80%, at the same time, does not damage the normal healthy cells. The researchers Mazur (30) found that a BET family protein inhibitor-JQ1 can inhibit the development of PDAC mice by inhibiting the activity of MYC and inflammatory signals.…”
Section: The Clinical Therapy Of Pancreatic Cancermentioning
confidence: 99%